2014
DOI: 10.1002/stem.1794
|View full text |Cite
|
Sign up to set email alerts
|

SMAD Signaling Regulates CXCL12 Expression in the Bone Marrow Niche, Affecting Homing and Mobilization of Hematopoietic Progenitors

Abstract: We recently demonstrated that ex vivo activation of SMAD-independent BMP4 signaling in hematopoietic stem/progenitor cells (HSPCs) influences their homing into the bone marrow (BM). We here assessed if alterations in BMP signaling in vivo affects adult hematopoiesis by affecting the BM niche. We demonstrate that systemic inhibition of SMAD-dependent BMP signaling by infusion of the BMP antagonist Noggin (NGN) significantly increased CXCL12 levels in BM plasma leading to enhanced homing and engraftment of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
3
25
0
1
Order By: Relevance
“…1g). As published before31, we sorted osteoblasts (lin − CD45 − Ter119 − CD51 + Sca-1 − ), mesenchymal stem cells (lin − CD45 − Ter119 − CD51 + Sca-1 + ) and endothelial progenitor cells (lin − CD45 − Ter119 − CD31 + Sca-1 + ) to analyse expression of Postn . We observed the highest expression of Postn in the endothelial progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…1g). As published before31, we sorted osteoblasts (lin − CD45 − Ter119 − CD51 + Sca-1 − ), mesenchymal stem cells (lin − CD45 − Ter119 − CD51 + Sca-1 + ) and endothelial progenitor cells (lin − CD45 − Ter119 − CD31 + Sca-1 + ) to analyse expression of Postn . We observed the highest expression of Postn in the endothelial progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…Adrenergic signaling reduces CXCL12 expression in the BM. affecting maintenance of HSC and the differential lineage commitment [7,95]. …”
Section: Correlations With Other Systems and Functionsmentioning
confidence: 99%
“…Tzeng and colleagues demonstrated that the stroma‐secreted CXCL12 (stromal cell‐derived factor‐1) keeps the HSCs in a quiescent state and maintains them in the osteoblastic niche . CXCL12 has been shown to be involved in hematopoietic progenitor cell homing and mobilization . A recent experimental study documented that under conditions of chronic variable stress in mice, sympathetic nerve fibers released surplus noradrenaline, which signaled bone‐marrow (BM) niche cells to suppress CXCL12 expression through the Adrβ3 …”
Section: Introductionmentioning
confidence: 99%